Metodologia para porte do sistema operacional Linux para sistemas embarcados - Souza, Osvaldo de (2007)
Embedded system development frequently uses the “trial and error” approach for Operating System (OS) porting,resulting in incomplete or inconsistent porting. In this work, we present a pioneer work addressing this issue. We propose a complete method for detecting OS parts that should be adjusted in order to port the OS into a new hardware platform. The proposed method combines information from the OS source-code and peculiarities of the new hardware platform, resulting in: a complete list of source-codes that must be adjusted; the interdependence between these source-codes; the priority order of modifications for each source-code; and an effort-based schedule to help planning the modifications. In addition, we propose an algorithm dealing with source-code’s cyclic references. Finally, we present a study-case based on an application developed according the proposed method.